2000
DOI: 10.2188/jea.10.1sup_90
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies and Circumstances of Falls in the National Institute for Longevity Sciences, Longitudinal Study of Aging (NILS-LSA)

Abstract: Frequencies and circumstances of falls were assessed among 1030 middle-aged and elderly people who participated in the NILS-LSA (National Institute for Longevity Sciences, Longitudinal Study of Aging) from November, 1997 to March, 1999 and responded to the questionnaires. The variables analyzed in the present study were demography and history of falls in the past one year. Circumstances of falls, e.g. time, location, activities associated with falls, cause of falls and degree of injury due to falls were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
96
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 9 publications
13
96
1
Order By: Relevance
“…Our results showed that falls were more common outdoors than indoors, and were more likely to be caused by extrinsic than intrinsic factors, which is consistent with previous findings (Niino et al 1995(Niino et al , 2000. Among our participants, 10% of those who fell sustained fractures, which is also consistent with previous findings (Aoyagi et al 1998;Niino et al 2000).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that falls were more common outdoors than indoors, and were more likely to be caused by extrinsic than intrinsic factors, which is consistent with previous findings (Niino et al 1995(Niino et al , 2000. Among our participants, 10% of those who fell sustained fractures, which is also consistent with previous findings (Aoyagi et al 1998;Niino et al 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Among our participants, 10% of those who fell sustained fractures, which is also consistent with previous findings (Aoyagi et al 1998;Niino et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 In 1 year, 59% of 91 self-reported falls were attributed to trips and slips in 50 independent, communitydwelling older people. 4 Because most falls in older people occur during locomotion, 5 the development of therapeutic interventions to enhance walking and reduce slip propensity is of great clinical importance.…”
mentioning
confidence: 99%
“…According to recent research reports of the Japanese Orthopedic Association, 70-80% of hip fractures occur by a fall from the standing position, and two-thirds of the falls take place inside the house [2]. This is actually quite different from the falls of general community dwellers, which occur mainly outside the house [3][4][5]. There have been several studies about the falls which lead to hip fracture but their situations have not been well investigated, and furthermore, most of the studies were done in Western countries [1,[6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%